2021
DOI: 10.3390/ma14226774
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Asymmetric Contact Resistances in Al-Contacted Mg2(Si,Sn) Thermoelectric Legs

Abstract: Thermoelectric generators are a reliable and environmentally friendly source of electrical energy. A crucial step for their development is the maximization of their efficiency. The efficiency of a TEG is inversely related to its electrical contact resistance, which it is therefore essential to minimize. In this paper, we investigate the contacting of an Al electrode on Mg2(Si,Sn) thermoelectric material and find that samples can show highly asymmetric electrical contact resistivities on both sides of a leg (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…Table shows the processing techniques and temperatures used in the literature to fabricate n-type Mg 2 (Si,Sn) with contacts. It has been reported that in n-type Mg 2 (Si,Sn) TE element fabrication, the material synthesis was carried out first and then separate contact fabrication processes were performed separately. ,,, In addition, the contact layer oxidation and removal process are inevitable due to two different processing sequences, adding additional manufacturing costs for device fabrication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table shows the processing techniques and temperatures used in the literature to fabricate n-type Mg 2 (Si,Sn) with contacts. It has been reported that in n-type Mg 2 (Si,Sn) TE element fabrication, the material synthesis was carried out first and then separate contact fabrication processes were performed separately. ,,, In addition, the contact layer oxidation and removal process are inevitable due to two different processing sequences, adding additional manufacturing costs for device fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the underlying scientific principles for properly selecting contact materials and developing bonding techniques are still limited. Several elemental metallic contacts, such as Cu, ,, Ag, ,, Ni, ,,, and Al, have been tried to achieve chemically and thermally stable joints on binary magnesium–silicon using different processing techniques. Few reported studies emphasized the use of binary ,, and ternary compounds to overcome the chemical reactivity of elemental metallic contacts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, contact resistances as low as ~43–59 mΩ.mm 2 were obtained in tetrahedrite legs/copper junctions. These values are close to the range reported for commercial TE devices (typically from 0.075 to 3.7 mΩ.mm 2 ) [ 51 , 52 , 53 ] and to other TE materials currently being studied, such as the skutterudites (~10–12 mΩ.mm 2 ) [ 54 ], the CoSb 3 compounds (~ 15 mΩ.mm 2 ) [ 55 ], and the Mg 2 (Si,Sn) legs (~1–20 mΩ.mm 2 ) [ 56 , 57 ].…”
Section: Computer Simulationsmentioning
confidence: 99%